Pars planitis: Epidemiology, clinical characteristics, management and visual prognosis - Ozdal, PinarCakar; Berker, Nilufer; Tugal-Tutkun, Ilknur (Journal of ophthalmic & vision research, 2015)
Pars planitis is an idiopathic chronic intermediate uveitis which predominantly affects children and adolescents, and accounts for 5-26.7% of pediatric uveitis. Although an autoimmune process with a genetic predisposition has been suggested, its etiology still remains unknown. The most common presenting symptoms are floaters and blurred vision. Diffuse vitreous cells, haze, snowballs and snowbanks are typical findings of pars planitis. Peripheral retinal vasculitis, optic disc edema and anterior segment inflammation are other well-known findings. Although pars planitis is known to be a benign form of uveitis in most cases, it may become a potentially blinding disease due to complications including cataract, cystoid macular edema, vitreous opacities and optic disc edema. Cystoid macular edema is the most common cause of visual morbidity. Band keratopathy, epiretinal membrane formation, vitreous condensation, neovascularizations, vitreous hemorrhage, retinal detachment, cyclitic membranes, glaucoma and amblyopia may develop as a consequence of the chronic course of the disease. Exclusion of infectious and non-infectious causes which may present with intermediate uveitis is of utmost importance before starting treatment. Treatment of pars planitis has been a controversial issue. There is no consensus specifically for treatment of cases with minimal inflammation and relatively good visual acuity. However, current experience shows that pars planitis may cause severe inflammation and needs an aggressive treatment. A stepladder approach including corticosteroids, immunosupressive agents, anti-tumor necrosis factor-alpha and pars plana vitrectomy and/or laser photocoagulation is the most commonly used method for treatment of pars planitis. Adequate control of inflammation and prompt detection of associated complications are crucial in order to improve the overall prognosis of the disease.